THE ROLE OF MULTISLICE COMPUTED TOMOGRAPHY IN THE DIAGNOSIS OF CEREBRAL STROKE (International Conference on Modern Science and Scientific Studies, 2025)
This annotation describes the importance of multislice computed tomography in the diagnosis of stroke. This imaging technology allows for fast and accurate evaluation of blood vessels and cerebral blood flow. Through non-contrast computed tomography, computed tomography angiography, and perfusion computed tomography, it is possible to determine the type and severity of the stroke. Automated software helps analyze results quickly and supports timely treatment decisions. Recent clinical studies have shown that this method is effective in selecting patients for endovascular treatment.